Health and Lifestyles - Blaxter Mildred (Tavistock Routledge, 1990)
An essential reading for students, researchers, and practitioners in community medicine, medical sociology, health education, social policy, and sociology. Acknowledgements, Introduction, The Health and Lifestyle Survey, What is Health?, The Measurement of Health, Social Circumstances and Health, Patterns of Behavior, Behavior and Health, Circumstances and Behavior and Health, Conclusions and Policy Implications, Appendices, Health: Questions and Measurements and the Formation of Indices, Social Integration and Support: Questions and Measures, Behavior: Questions and the Formation of Indices, Attitudes: Questions and Measures, References, Index.